2020
DOI: 10.1111/aji.13342
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic endometriosis and natural killer cell immunity

Abstract: Endometriosis is a chronic disease that commonly affects women in their reproductive age. It has been reported that the infertility due to endometriosis is largely caused by pelvic adhesion, oocyte damage, and so on. There are several causes of endometriosis including bacterial infections, immunological abnormalities, epigenetics, and aberrant DNA methylation. The natural killer (NK) cells present in the peritoneal fluid express CD16 and CD56. They also express NK cell inhibitory receptors and activating recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…This is true for both IL-1α and IL-1β levels, although their effects on endometrial cells differ [74]. Changes in immune cell function in the peritoneal fluid and cytokine production, including IL-1, have been reported to be one cause of infertility [76]. Increased levels of IL-1α are observed in the peritoneal fluid of women with endometriosis.…”
Section: Interleukin 1 (Il-1)mentioning
confidence: 99%
“…This is true for both IL-1α and IL-1β levels, although their effects on endometrial cells differ [74]. Changes in immune cell function in the peritoneal fluid and cytokine production, including IL-1, have been reported to be one cause of infertility [76]. Increased levels of IL-1α are observed in the peritoneal fluid of women with endometriosis.…”
Section: Interleukin 1 (Il-1)mentioning
confidence: 99%
“…Some studies have shown that the natural receptor for cytotoxicity, NKp46, and the cell surface marker for cytotoxicity, CK107a, are significantly reduced in the peritoneal fluid of patients with endometriosis. In contrast, the NKG2A receptor, an inhibitory cytotoxic receptor, is overexpressed in peritoneal NK cells [57,67,68]. The increase in cytokines in the peritoneal fluid, as well as those secreted by the ectopic endometrial tissue itself, also interfere with the functionality of NK cells.…”
Section: Dysfunction Of the Innate Immune System And Its Relationship...mentioning
confidence: 99%
“…Following changes in the properties and function of NK cells, immune surveillance in the peritoneal cavity was impaired, leading to increased survival of EC endometrial cells (Figure 1). 56 Xuan‐Tong Liu et al., suggested that ESCs partly up regulated the expression of IDO in NK cells by secreting TGF‐β, hence reducing the expression of activating receptors and increasing the expression of IL‐ 10 by these cells, and eventually leading to a decrease in the lethal activity of NK cells 57 . The percentage of NK cells in the PB of patients does not differ, but in the case of PF, contradictory results have been reported 58 .…”
Section: Innate Immune Cells In Endometriosismentioning
confidence: 99%